Deep trouble - Stine, R. L. (New York : Scholastic, 2008)
While visiting his uncle, Dr. Deep, on a tiny Caribbean island, Billy goes exploring underwater, ignoring warnings to stay away from the coral reef, and is stalked by a half-human, half-fish predator.
"Now with bonus features!"--Cover.
5.4
5-8
Keywords: Horror tales; Mermaids -- Juvenile fiction; Monsters -- Juvenile fiction; Horror stories; Mermaids -- Fiction; Monsters -- Fiction; Horror fiction; Mermaids and mermen -- Fiction; Monsters -- Fiction